Gambaran Sanitasi Total Berbasis Masyarakat (STBM) di Kota Depok Jawa Barat Tahun 2023 - R, Alya Aulia; Wardani, Riastuti Kusuma (Journal of Religion and Public Health, 2023)
AbstractCommunity Based Total Sanitation (CBTS) is a community empowerment program to encourage people to change sanitation and hygiene behavior. CBTS’s output indicators are that every household has access to basic sanitation and is free from open defecation, and every household can manage drinking water, food and household waste safely and correctly. The purpose of this study was to find out the description of Community Based Total Sanitation (CBTS) in Depok City, West Java in 2023. The research design was cross sectional which took place in June August 2023. This study is using secondary data from Depok’s District Health Office with 36.276 samples. The results of statistical tests show that CBTS Pillar 1 in Depok City is 98% Stop Open Defecation, CBTS Pillar 2 is 93.5% Washing Hands with Soap, CBTS Pillar 3 is 64.7% Unsafe Household Drinking Water and Food Processing, Pillar 4 CBTS is 62.9% Unsafe Household Waste Processing, and Pillar 5 STBM is 77.8% Unsafe Household Liquid Waste Processing. The CBTS in Depok City in 2023 has not been 100% achieved. There is a need for guidance to the community on good and correct household sanitation steps and the fulfillment of the facilities needed to realize CBTSs. Keywords: Environmental Sanitation, Household Environmental Sanitation, CBTS